The Availability indicators of Strategic Planning from the University’ Teaching Staff Members point of view - Afield Study at Tishreen University- - Mohamed , Mahmoud Ali; Mahmoud , Noura Hasan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The current research aims to study the Availability indicators of Strategic Planning from the Teaching Staff Members point of view at Tishreen University, and also and to study the different of such attitudes according to variables (kind of Faculty, the scientific degree, the experience). and to achieve the objectives of this research the objectives of this research, questionnaire was built, consisted (54) items, included four areas, has been applied on sample (196) Teaching Staff Members at Tishreen University during the academic year of (2018 - 2019). Descriptive analytical methodology was used, and Validity of the questionnaire was established though a jury of (7) of the teaching staff at Damascus and Tishreen Universities. Pilot sample consisted of (26) Teaching Staff Members, Reliability was established by Cronbach – Alpha Reliability (0.975) and (0.987) at Spearman-Brown. The research results showed that the Availability indicators of Strategic Planning from the Teaching Staff Members point of view at Tishreen University were middle. In fact there are found differences about the Availability indicators of Strategic Planning at Tishreen University according to variable scientific degree in favor of the Assistant Professor and Professor, but there are no found differences according to these variables (kind of Faculty, experience). The research suggested interesting to establish concept of Strategic Planning, and employment it in carrying out of labor market requests.